Detection of short-term activity avalanches in human brain default mode network with ultrafast MR encephalography - Rajna, Zalán; Kananen, Janne; Keskinarkaus, Anja; Seppänen, Tapio; Kiviniemi, Vesa (Frontiers in Human Neuroscience, 2015)
!! According to author guidelines, 2000 characters are allowed for an abstract. Our abstract is under 2000 characters, but over 200 words, thus the online form is limiting our submission. See manuscript for the full abstract. Recent studies pinpoint visually cued networks of avalanches with MEG/EEG data. Co-activation pattern analysis can be used to detect single brain volume activity profiles and hemodynamic fingerprints of neuronal avalanches as sudden high signal activity peaks in classical fMRI data. In this study, we aimed to detect dynamic patterns of brain activity spreads with the use of ultrafast MR encephalography (MREG). MREG achieves 10 Hz whole brain sampling, allowing the estimation of spatial spread of an avalanche, even with the inherent hemodynamic delay of the BOLD signal. We developed a novel computational method to separate avalanche type fast activity spreads from motion artifacts, vasomotor fluctuations and cardio-respiratory noise in human brain default mode network. Reproducible and classical DMN sources were identified using spatial ICA prior to advanced noise removal in order to assure that ICA converges to reproducible networks. Brain activity peaks were identified from parts of the DMN, and normalized MREG data around each peak were extracted individually to show dynamic avalanche type...